Colonoscopy and polypectomy: beside age, size of polyps main factor for long-term risk of colorectal cancer in a screening population - Halfter, Kathrin (J Cancer Res Clin Oncol, 2021)
PURPOSE: Despite national and international guideline recommendations, few studies have been conducted to estimate the impact of colonoscopy screening on long-term colorectal cancer incidence. Aim of this study was to determine the long-term impact of a full colonoscopy with polypectomy on colorectal cancer incidence in a large screening population. METHODS: In this prospective observational cohort study, a total of 10,947 colonoscopy screening participants from within the scope of the Munich Cancer Registry were consecutively recruited from participating gastroenterology practices and their subsequent colorectal cancer incidence assessed. Predictive factors associated with colorectal cancer were also evaluated in univariate and multivariate analyses. RESULTS: After a median follow-up of 14.24 years (95% CI [14.21–14.25]), 93 colorectal cancer cases were observed. This is equivalent to a truncated age-standardized rate of 69.0 (95% CI [43.3–94.7]) for male and 43.4 (95% CI [29.4–57.5]) for female participants (≥ 50 years at colonoscopy). The ratio of this observed to the expected rate from cancer registry data showed a 67% decrease in colorectal cancer incidence in the male and 65% in the female participants (p < 0.0001). In multivariate analysis of screening patients, age at screening (p < 0.0001) was the main predictive factor for colorectal cancer. In the subgroup with positive polyp findings, age (p < 0.0001) and the polyp size (p = 0.0002) were associated with colorectal cancer. CONCLUSION: These results underline the significance of a full colonoscopy screening combined with polypectomy in reducing the total disease burden of colorectal cancer. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00432-021-03532-7.